The Aging Narcissus: Just a Myth? Narcissism Moderates the Age-Loneliness Relationship in Older Age - Carter, Gregory L.; Douglass, Melanie D. (Frontiers in Psychology, 2018)
Objective: Recent research has indicated that sub-clinical narcissism may be related to positive outcomes in respect of mental and physical health, and is positively related to an extended lifespan. Research has also indicated narcissism levels may decline over the lifespan of an individual. The aims of the present study were to investigate these issues, exploring age-related differences in levels and outcomes of narcissism. Specifically, narcissism’s relationship with loneliness, a deleterious but pervasive state among older-age individuals, was assessed. Method: 100 middle-aged (MAGE = 48.07; SD = 5.27; 53% female) and 100 older-aged participants (MAGE = 70.89; SD = 5.97; 51% female) completed the 40-item Narcissistic Personality Inventory and the UCLA Loneliness Scale, Version 3. Results: Older-age participants had significantly lower levels of narcissism, and significantly higher levels of loneliness than middle-aged participants. Age and narcissism significantly predicted self-reported loneliness levels, with narcissism moderating the relationship between age and loneliness. Conclusions: This study supports existing work, indicating that a degree of narcissism is of benefit to psychological functioning in respect of age-related loneliness, and is found to be a protective factor in mental health.